2021
DOI: 10.1002/brb3.2330
|View full text |Cite
|
Sign up to set email alerts
|

Antiseizure medications for post‐stroke epilepsy: A real‐world prospective cohort study

Abstract: Background and purpose:The management of post-stroke epilepsy (PSE) should ideally include prevention of both seizure and adverse effects; however, an optimal antiseizure medications (ASM) regimen has yet been established. The purpose of this study is to assess seizure recurrence, retention, and tolerability of older-generation and newer-generation ASM for PSE. Methods: This prospective multicenter cohort study (PROgnosis of Post-Stroke Epilepsy [PROPOSE] study) was conducted from November 2014 to September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 43 publications
(75 reference statements)
0
25
0
Order By: Relevance
“…Also, indirect comparisons of LEV and LTG did not reveal differences in seizure freedom (odds ratio 0.86; 95% CI: 0.15.− 4.89) [10]. However, significantly lower mortality was seen with LTG monotherapy compared to therapy with CBZ [18] and overall, therapy with newer ASMs showed better seizure control and better tolerability compared with older ASMs [19].…”
Section: Discussionmentioning
confidence: 91%
“…Also, indirect comparisons of LEV and LTG did not reveal differences in seizure freedom (odds ratio 0.86; 95% CI: 0.15.− 4.89) [10]. However, significantly lower mortality was seen with LTG monotherapy compared to therapy with CBZ [18] and overall, therapy with newer ASMs showed better seizure control and better tolerability compared with older ASMs [19].…”
Section: Discussionmentioning
confidence: 91%
“…This study was conducted as a single-center sub-analysis of the PROgnosis of Post-Stroke Epilepsy (PROPOSE) study (UMIN000019940), consisting of (i) a preceding single-center retrospective cohort in the National Cerebral and Cardiovascular Center (NCVC) between January 2011 and October 2014 and (ii) a multi-center (eight sites) prospective cohort between November 2014 and September 2018 ( 3 ). PROPOSE was a non-interventional observational cohort study, enrolling patients with PSE admitted to each stroke center.…”
Section: Methodsmentioning
confidence: 99%
“…Poststroke epilepsy (PSE) is the most common type of epilepsy in the elderly ( 1 ) and is related to poor prognosis in poststroke survivors ( 2 ). Diagnosis of PSE is often challenging in cases which present with non-convulsive seizures and show no epileptiform abnormalities on electroencephalography (EEG) ( 3 ). Our recent study identified prolonged postictal hyperperfusion in PSE using postictal-interictal (P-I) subtraction perfusion single-photon emission computed tomography (SPECT) co-registered to magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…All PSE diagnoses were made by board-certified epileptologists or neurologists at each institution based on the seizure semiology, EEG findings, and brain imaging findings (CT, MRI, and/or SPECT). 11 Among patients with PSE enrolled in the PROPOSE study, this study only included patients with a first-ever seizure to ensure a uniform duration between the onset and outcome assessments.…”
Section: Study Design and Participantsmentioning
confidence: 99%